Perinatal outcome associated with oligohydramnios in third trimester - Chaudhari, Kamlesh R.; Chaudhari, Kushagra R.; Desai, Omkar M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: We aimed to evaluate the effect of Oligohydramnios on fetal outcome in terms of fetal distress, Meconium staining of amniotic fluid, birth weight, Apgar score of newborn babies, NICU admission, early neonatal morbidity and mortality. Methods: This was a prospective study of 156 antenatal patients booked at K. J. Somaiya medical college and research centre during the year January 2012 to December 2013 with gestational age between 30-40wks with AFI<5cms with intact membranes were analyzed for perinatal outcome. Results: The Caesarian section rate for fetal distress was 41% in patients with Oligohydramnios. Meconium staining of amniotic fluid was found in 30.7% patients. APGAR score at 5 minutes <7 was found in 6 patients (3.8%). Conclusions: Oligohydramnios has significant correlation with Caesarean section for fetal distress and low birth weight babies. Oligohydramnios is associated with high rate of pregnancy complication and increased perinatal morbidity and mortality. Oligohydramnios is a frequent occurrence demand careful evaluation, intensive parental counseling, fetal surveillance and proper antepartum and intrapartum care.